Taxonomic study of some Afrotropical erythroneurine leafhoppers (Hemiptera: Cicadellidae: Typhlocybinae) - Cao, Yanghui; Dietrich, Christopher H.; Dmitriev, Dmitry A.; Zhang, Yalin (Zootaxa, 2020)
Six Afrotropical genera of the leafhopper tribe Erythroneurini are redescribed and two new genera, Laminaris gen. nov. and Projecta gen. nov. are established. Sixteen new species are described and illustrated: Laminaris angusta sp. nov., Laminaris cuspidatima sp. nov., Laminaris serrata sp. nov., Laminaris tenuis sp. nov., Projecta auriculata sp. nov., Projecta brevis sp. nov., Projecta depressa sp. nov., Projecta draciformis sp. nov., Accacidia obunca sp. nov., Imbecilla bifurca sp. nov., Imbecilla spinalis sp. nov., Lublinia anchoroides sp. nov., Molopopterus hastata sp. nov., Molopopterus ugandica sp. nov., Lamtoana exigua sp. nov. and Nsesa cameroonica sp. nov. Nsesa Dworakowska, 1974 is newly recorded from Cameroon; Nsimbala Dworakowska, 1974 and Szymczakowskia Dworakowska, 1974 from the Central African Republic; Lublinia Dworakowska, 1970, Lamtoana Dworakowska, 1972 and Ivorycoasta Dworakowska, 1972 from the Republic of Congo. Keys to species of the genera Accacidia Dworakowska, Imbecilla Dworakowska, Lublinia Dworakowska, Molopopterus Jacobi, Lamtoana Dworakowska and Nsesa Dworakowska are also given.